Characteristic changes in malt, wort, and beer produced from different Nigerian rice varieties as influenced by varying malting conditions - Ofoedu,Chigozie E.; Akosim,Chibugo Q.; Iwouno,Jude O.; Obi,Chioma D.; Shorstkii,Ivan; Okpala,Charles Odilichukwu R. (PeerJ, 2021)
Gluten-free beer could be produced with rice, although the latter would primarily serve as adjunct in combination with barley malt in today’s brewing. However, the recent growing realisation of the potential and applications of rice malt for brewing an all-rice malt beer through varying malting conditions cannot be overlooked. In this study, therefore, the characteristic changes in malt, wort, and beer from different Nigerian rice varieties (FARO 44, FARO 57, NERICA 7) as influenced by varying malting conditions (steeping duration (18, 24 and 30 h), germination periods (2, 3 and 4 days) and kilning temperatures (50 and 55 °C)), were investigated. Rice (grain) samples were examined by thousand kernel weight (TKW), germinative energy (GE), germinative capacity (GC), and degree of steeping (DoS). To ensure that rice wort/beer with unique beer style and enhanced attributes, comparable to barley wort/beer is produced, malting conditions that produced rice malts with peak diastatic power (DP), cold water extract (CWE), and hot water extract (HWE) were selected. Peak DP, CWE and HWE were obtained at FARO 44 (18 h steeping, 3 days germination, 55 °C kilning (S18G3K55°)), FARO 57 (30 h steeping, 2 days germination, 50 °C kilning (S30G2K50°)) and NERICA 7 (24 h steeping, 3 days germination, 55 °C kilning (S24G3K55°)). Selected malts were further tested for moisture content, total nitrogen, malt yield and malting loss and subsequently progressed to wort and beer production. Wort’s pH, total soluble nitrogen (TSN), brix, kolbach index (KI), free amino nitrogen (FAN), dextrose equivalent (DE), original extract (OE) and sugar profile were determined, as well as beer’s pH, colour, apparent extract (AE), alcohol by volume (%ABV), turbidity and sensory attributes. Rice grain varied significantly (p < 0.05) in TKW, GE, GC and DoS across varieties. Despite wort’s pH, TSN, DE, OE as well as beer pH, colour, AE and turbidity resembling (p > 0.05) across varieties, wort’s brix, KI, FAN, sugar profile as well as beer’s %ABV, differed significantly (p < 0.05). Sensory attributes of appearance, colour, mouthfeel, and overall acceptability in beer differed noticeably (p < 0.05), except for aroma and taste (p > 0.05). Overall, the rice beer, though very slightly hazy, represented a pale yellow light lager, which is indicative of its peculiar beer style. Besides increased DP and enhanced hydrolysis, varying malting conditions of current study could serve as a pathway of reducing the cost of exogenous (commercial) enzymes or barley malt imports, together with decreasing barley’s dependency for brewing in the tropics.
Keywords: Malting conditions; Rice malt; Rice beer; Rice wort; Mashing process